Guia De Auditoria Interna Para La Evaluación De Riesgos En Los Inventarios De La Empresa Electrimapiri S.A E.S.P Basada En La Nia 501 - Veloza Olaya, Faiber Danilo; Rodriguez Acosta, Karen Judith (Universidad Antonio Nariño, 2022)
This work is focused on the elaboration of an internal audit guide for future readers and researchers who are interested in obtaining more knowledge on this subject that is based on the International Auditing Standard on Inventories (ISA 501) for revision, control and supervision of the energy company in Mapiripán meta called Electrimapiri S.A E.S. P for inventory control.